Chromatographic Methods to Analyze Geometrical and Positional Isomers of Fatty Acids : A Review - N. M., Aini; M. M., Yusoff; Azhari, H. Nour (2009)
Problems in analyzing fatty acids are to obtain good esolution of geometrical and positional isomers. In GCMS analysis, common derivative of fatty acids such as fatty acids methyl ester (FAME) will not give mass spectra that indicative of the true structure of fatty acids, thus structure elucidation of fatty acids will be misled. This review describes chromatographic methods to obtain good resolution of geometrical, positional isomer of fatty acids and to determine the double bond position in fatty acids. Methods that are described are gas chromatography (GC), gas chromatography mass spectrometry (GCMS),thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) impregnated with silver ion. Derivatization methods to determine double bond position of fatty acids are also described. Applications, advantages and drawbacks of every method are discussed.